Sensitivity Study of Planetary Boundary Layer Parameterization Schemes for the Simulation of Tropical Cyclone ‘Fani’ Over the Bay of Bengal Using High Resolution Wrf-Arw Model (Journal of Engineering Science, 2020)
Comprehensive sensitivity analyses on physical parameterization schemes of WRF-ARW (V3.8.1) model have been carried out for the simulation of Tropical Cyclone (TC) Fani that formed in the Bay of Bengal (BoB) and crossed the Bangladesh and Odisha coast of India on 3rd May 2019. Global Forecasting System (GFS) data 1⁰ and 0.25⁰ from National Centre for Environment Prediction (NCEP) is used as initial and lateral boundary conditions. The six different Planetary Boundary Layer (PBL) schemes used in this research are YSU, BouLac, TEMF, Shin-Hong, GBM and MRF. The meteorological parameters, which have been studied to identify the effect of PBL during the propagation and movement of TC Fani are Estimated Central Pressure (ECP), Maximum Wind Speed (MWS) at 10m height, average relative humidity (%), temperature (⁰C) and potential temperature (0K) at 2m height, Modified Convective Available Potential Energy (MCAP), average PBL height and average high clouds (%). The area considered for these averages are 82-92 ⁰E and 7-22 ⁰N inside the model domain. The simulated ECP by TEMF scheme are 930, 932, 937, 929, 944 and 932 hPa for the Initial Conditions (ICs) at 0000 UTC of 27, 28, 29, 30 April, and 01 May and 02 May, respectively and observed ECP was 932 hPa. The intensity of pressure fall by the TEMF scheme is similar to that observed up to the time of crossing the land of TC Fani. The MWS simulated by the TEMF scheme is almost similar to that of the observed MWS at 10m height and all other schemes have simulated much lower MWS. The temperature at 2m height is positively correlated with the ECP and MWS at 10m height. The TEMF scheme has simulated maximum high clouds for all ICs and for all through the simulation time. The error was systematic for all PBL schemes for the ICs at 0000 UTC of 30 April at 0.25⁰ and 1⁰ GFS data but the track error was much less for 1⁰ GFS data than that of 0.25⁰ GFS data. The TEMF scheme has simulated the most deviated track and MRF scheme has simulated less deviated track for all through the simulation. The study has shown large variations of track and intensity among the different PBL schemes. The PBL schemes have a major impact on the track and intensity of TC Fani. The intensity simulated by the TEMF scheme is better but the track error is higher than that of other schemes.Journal of Engineering Science 11(2), 2020, 1-18